2010
DOI: 10.1093/neuonc/nop068
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule kinase inhibitors in glioblastoma: a systematic review of clinical studies

Abstract: The efficacy of small-molecule kinase inhibitors has recently changed standard clinical practice for several solid cancers. Glioblastoma is a solid cancer that universally recurs and unrelentingly results in death despite maximal surgery and radiotherapy with concomitant and adjuvant temozolomide. Several clinical studies using kinase inhibitors in glioblastoma have been reported. The present study systematically reviews the efficacy, toxicity, and tissue analysis of small-molecule kinase inhibitors in adult p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
127
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 67 publications
0
127
0
Order By: Relevance
“…[133,134] Unfortunately, the overall response rate of GBMs to kinase inhibitors in clinical trials has been poor so far. [135] One reason for these disappointing results may be inadequate trial design. Systematic flaws such as small sample sizes, absent control groups and unverified drug activity have been reported in the past.…”
Section: Clinical Trials Of Kinase Inhibitors In Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…[133,134] Unfortunately, the overall response rate of GBMs to kinase inhibitors in clinical trials has been poor so far. [135] One reason for these disappointing results may be inadequate trial design. Systematic flaws such as small sample sizes, absent control groups and unverified drug activity have been reported in the past.…”
Section: Clinical Trials Of Kinase Inhibitors In Glioblastomamentioning
confidence: 99%
“…Systematic flaws such as small sample sizes, absent control groups and unverified drug activity have been reported in the past. [135] Therefore, various changes in study design have been proposed to improve the reliability of the results. Clinical trials enriched for patients with an aberrant kinase target are likely to give a better picture of the overall performance of a particular inhibitor.…”
Section: Clinical Trials Of Kinase Inhibitors In Glioblastomamentioning
confidence: 99%
“…Anti-RTK-based strategies using small molecule kinase inhibitors or antibodies have been tested in clinical trials for patients with malignant glioma. These were focused on the inhibition of excessive RTK activity and thus of the downstream cellular signaling cascades that are responsible for enhanced proliferation, angiogenesis and the survival of cancer cells (3,(5)(6)(7). Among others, two major intracellular signaling pathways that are activated by RTKs and are co-opted in tumor cells are the Ras/MAPK and PI3K/Akt/mTOR pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Imatinib has shown remarkable effects not only in patients with chronic myeloid leukemia (CML) and Bcr-Abl activation, but has also been proven to inhibit c-Kit-and PDGFRAmediated signaling and to improve survival in patients with gastrointestinal stromal cell tumors (15) and hypereosinophilic syndrome (16). However, phase I/II clinical studies with single-agent imatinib have failed to demonstrate significant clinical effects in patients with malignant glioma (5,17). Although results from phase II studies on the agent in combination with hydroxyurea, have suggested beneficial effects and have supported the initiation of a randomized clinical trial (18), this trial was eventually halted due to proven lack of efficacy (7).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Testing for EGFR expression and/or amplification may also prove useful from a therapeutics perspective, assuming that an anti-EGFR drug can be developed that has significant therapeutic effects. 7,8 Several retrospective studies 9 -14 have tested the correlation between EGFR expression in WHO gradeadjusted gliomas and patient survival, with conflicting data. Herein, we describe the results of EGFR expression analysis from a prospective cohort of 750 infiltrative gliomas covering WHO grades II to IV, including its ability to predict EGFR amplification and its correlation with patient survival.…”
mentioning
confidence: 99%